A scientific model of pantheism. Issue 3 (2nd September 2016) - Ostrowick, John
Abstract : Given the scientific possibility of Boltzmann Brains, and the theory from philosophy of mind known as Functionalism, it is quite possible to construct a model of pantheism which is not as implausible as restricted theism or traditional models of pantheism. The aim of this article is to explain how this might work, but also to say why, in the end, it will not do the same job as restricted theism, even if it turned out to be true. The article does not aim to defend its premises, such as pantheism or functionalism, in more than a cursory way; the conclusions of the article are tentative and conditional: if functionalism is true, then physicalist pantheism may be true.